Hospitalist Vs. Non-Hospitalist Care Outcomes and Costs for Medicare Beneficiaries Discharged to Skilled Nursing Facilities in 2012–2014 - Ryskina, Kira L. (J Gen Intern Med, 2019)
BACKGROUND: Hospitals are increasingly at risk for post-acute care outcomes and spending, such as those in skilled nursing facilities (SNFs). While hospitalists are thought to improve patient outcomes of acute care, whether these effects extend to the post-acute setting in SNFs is unknown. OBJECTIVE: To compare longer term outcomes of patients discharged to SNFs who were treated by hospitalists vs. non-hospitalists during their hospitalization. DESIGN: This was a retrospective cohort study. PARTICIPANTS: Participants are Medicare fee-for-service beneficiaries over 66 years of age who were hospitalized and discharged to a SNF in 2012–2014 (N = 2,839,779). MAIN MEASURES: We estimated the effect of being treated by a hospitalist on 30-day rehospitalization and mortality, 60-day episode Medicare payments (Parts A and B), and successful discharge to community. Patients discharged to the community within 100 days of SNF admission who remained alive and not readmitted to a hospital or SNF for at least 30 days were considered successfully discharged. All outcomes were adjusted for demographics and clinical characteristics. To account for heterogeneity across facilities, we included hospital fixed effects. KEY RESULTS: The 30-day rehospitalization rate was 17.59% for hospitalists’ vs. 17.31% for non-hospitalists’ patients (adjusted difference, 0.28%; 95% CI, 0.13 to 0.44). Sixty-day payments were $26,301 for hospitalists’ vs. $25,996 for non-hospitalists’ patients (adjusted difference, $305; 95% CI, $243 to $367). There was a non-significant trend toward lower successful discharge to the community rate (adjusted difference, − 0.26%; 95% CI, − 0.48 to − 0.04) and lower mortality for patients of hospitalists (adjusted difference, − 0.12%; 95% CI, − 0.22 to − 0.02). CONCLUSIONS: Among hospitalized Medicare beneficiaries who were discharged to SNFs, readmissions and Medicare costs were slightly higher for stays under the care of hospitalists compared with those of non-hospitalist generalist physicians, but there was a non-significant trend toward lower mortality. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05459-9) contains supplementary material, which is available to authorized users.